Implicit theories, organizational design, and effectiveness - Rico, Ramón; Fernández-Ríos, Manuel; Rascado, Paloma; Sánchez-Manzanares, Miriam (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In this study, we aimed to test a model to understand the process of organizational design from a cognitive perspective. In a quasi-experiment field, we gathered the implicit theories, from the members of two organizations, concerned with the organizational design parameters estimated as more or less necessary to satisfy different areas of organizational effectiveness. According with these data, we proposed specific changes in the design of one organization in its decentralization, formalization, and integration and coordination processes. The results show significant differences in perceived organizational effectiveness between the redesigned organization and the non-redesigned one.